Keystone perforator island flaps in the reconstruction of lower limb defects resulting from shrapnel and mine-explosive combat injuries. Case series - Sliesarenko, S. V.; Badiul, P. A.; Rudenko, O. I.; Romanshuk, M. I. (General Surgery, 2023)
In the conditions of warfare in Ukraine, the question of providing medical services to injured civilian and military is especially relevant and severe. In plastic surgeons` professional activities, the task is to restore extensive and deep wound defects in a short term and with a high degree of damaged organ`s restoration, especially supporting function. In this article the authors describe their experience with local keystone perforator island flaps, which are used to reconstruct skin and soft tissue defects of the lower limbs caused by combat injuries. Patients and methods. The authors conducted a retrospective review of 49 keystone perforator flaps for 28 patients (26 men and 2 women) who received treatment in the clinic for bullet, shrapnel, and mine‑explosive injuries between 2014 and 2022. Results. In all cases, extensive wound defects were completely closed during a single‑stage surgical procedure, and the patients were discharged after recovery. Non‑critical complications required secondary sutures in two cases (4%), extending the duration of treatment by 6 days. The time spent in the operating room on the transposition of one flap ranged from 40 to 95 min (mean: 67 min). Conclusions. The findings of the study show that local keystone perforator island flaps are highly effective in the successful reconstruction of lower limb defects caused by combat wounds. The keystone perforator island flap technique requires basic preoperative preparation of the patient, is easy‑to‑use, and exhibits a fairly high level of reliability at the same time. In most cases, keystone perforator island flaps provide primary and single‑stage closure of a large defect in the thigh, in the area of the knee joint, and in the lower leg in the absence of secondary defects that are common at donor sites when alternative techniques are chosen.